THE STARS OF THE LOWER PART OF MAIN SEQUENCE - Mishenina, T. V.; Belik, S. I.; Usenko, I. A.; Bienayme, O.; Soubiran, C.; Kovtyukh, V. V.; Korotin, S. A. (Одеські астрономічні публікації, 2007)
Atmospheric parameters (Teff , log g, [Fe/H], Vt), Li, and volatile (O, Na, Al, Zn) and refractory (Si, Ti, V, Cr, Co and Ni) element abundances in 133 stars belonging to the low part of MS have been determined. Among them about 30 stars are the variable stars of BY Dra type, for which the determination of the chemical composition was made for the first time. The effective temperatures Teff were estimated by the line depth ratio method. The surface gravities log g were determined by two methods (ionization balance of iron and using parallaxes). The abundances of lithium and oxygen were determined by the calculation of synthetic spectrum. The comparison of volatile and refractory element abundances in variable stars and other stars was made. We have found that the behaviour of the abundances of the majority of elements in MS stars and spotted stars does not differ. The Li is detected in 65 BY Dra stars and in 26 of MS stars. The Li abundance in variable stars is higher than in MS dwarfs.